2008
DOI: 10.1136/ard.2007.086652
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased telomere lengths in limited scleroderma, with a lack of age-related telomere erosion

Abstract: Objectives: Telomere erosion, a feature of biological ageing, is implicated in a wide range of diseases. Its impact on autoimmune diseases remains unclear although autoantibodies against many telomere nucleoprotein components are prevalent in these diseases. We aimed to assess if telomere biology was abnormal in a cohort of patients with limited cutaneous systemic sclerosis (lcSSc). Methods: Telomere lengths in peripheral blood leucocytes (PBL) were determined using Southern blotting methods in a cohort of lcS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…Thus, many studies have observed that accelerated telomere loss is a common feature of systemic autoimmune disease, such as systemic lupus erythematosus or rheumatoid arthritis [37], and local or systemic fibrotic conditions, such as scleroderma [38], idiopathic pulmonary fibrosis [39] and cirrhosis [32,36]. The combination of inflammatory, autoimmune and fibrotic processes in PSC, increases the potential for a telomeretelomerase system dysfunction, as found in our study.…”
Section: Discussionsupporting
confidence: 47%
“…Thus, many studies have observed that accelerated telomere loss is a common feature of systemic autoimmune disease, such as systemic lupus erythematosus or rheumatoid arthritis [37], and local or systemic fibrotic conditions, such as scleroderma [38], idiopathic pulmonary fibrosis [39] and cirrhosis [32,36]. The combination of inflammatory, autoimmune and fibrotic processes in PSC, increases the potential for a telomeretelomerase system dysfunction, as found in our study.…”
Section: Discussionsupporting
confidence: 47%
“…First, the presence of underlying metabolic disorders mentioned above. Second, accelerated telomere loss has been implicated in other local or systemic fibrotic conditions, such as scleroderma [MacIntyre et al, 2008] and idiopathic pulmonary fibrosis [Armanios et al, 2007]. Cirrhosis from any etiology, including CC, is another local fibrotic disease with systemic implications and, thus, is expected to cause telomere shortening, as indeed was demonstrated previously [Wiemann et al, 2002;Chaiteerakij and Roberts, 2011].…”
Section: Discussionmentioning
confidence: 79%
“…In various tissues and cell-subtypes, accelerated cell turnover is inversely associated with replicative senescence. In disorders involving accelerated oxidative injury and chronic immune system activation as the main manifestation, such as systemic lupus erythematosus,33 rheumatoid arthritis32 and systemic sclerosis,34 enhanced cell turnover and telomere erosion has been extensively described. Furthermore, we observed no significant TL difference in treated patients with gout compared with patients without treatment.…”
Section: Discussionmentioning
confidence: 99%